Connecting animals and children in early childhood - Selly, Patty Born (Redleaf Press, 2014)
"Animals appeal to children's curiosity, bring enthusiasm to their learning, and enrich their daily experiences. This book emphasizes the reasons why children's interactions and connections with animals are important, and it describes the valuable social-emotional development that results. It combines research, anecdotes, and a number of creative ideas that caregivers and educators can use to create authentic experiences for children age three through eight. These ideas incorporate all kinds of animals in a variety of ways-including adaptations if live animals are not permitted in the child care or learning environment. Patty Born Selly is Executive Director of the National Center for STEM Elementary Education at St. Catherine University in St. Paul, Minnesota. In 2005, she founded Small Wonders, an educational consulting company offering services to schools, faith-based communities, and other organizations wishing to incorporate STEM and nature education to their programs. Patty also serves as adjunct faculty at Metropolitan State University in Minnesota, where she teaches classes on children and nature and environmental education."--